Effect of microwave sintering on the microstructure and tribological behavior of Ti-3Al-2.5 V-xWC composite. (October 2022) - Muthusamy, P.; Mohanraj, M.; Ramkumar, T.; Selvakumar, M.
Abstract: Ti-3Al-2.5 V-xWC composite was fabricated through Microwave Sintering (MS) technique. Tungsten Carbide (WC) with 0.5, 1.0, 1.5, 2.0 and 2.5 (by weight %) were dispersed in matrix. Specimens were densified using microwave sintering technique at 1200 °C. The fabricated composites were characterized using Field Emission Scanning Electron Microscope (FE-SEM) with Energy Dispersive Analysis (EDS) line mapping. Densification, Microstructure, mechanical properties and dry sliding wear behavior were examined. The results revealed that higher density after sintering, improved the mechanical and wear behavior. It reached maximum hardness of 298VHN, Wear rate of 0.33 × 10 −4 mm 3 /m and Coefficient of Friction of 0.45 for Ti-3Al-2.5 V-2WC composite. It was also established that microwave sintering with less sintering time helps to reduce the defect during sintering.